MOTTVATION FOR BNTREPRENEURS USING FRANCHISING AS GROWTH STRATEGY. A cose study of Monsterjelly and Semerbak Coffee - , Paksi Dewandaru; , Nurul Indarti, Sivilokonom. Cand. Merc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The current world economic situation forces entrepreneur to become smarter in selecting strategy to grow their business. Franchise is considered to be an effective instrument for investment, as only with limited start-up capital, the venture can provide with continuous earnings, providing its well operated. Franchising is an entrepreneurial option toward the creation and development of ventures. Monsterjelly and Semerbak Coffee are some of the companies that use franchising as their growth strategies. This paper analyzes these two companies to have better understanding about the motive why the company chooses to franchise their business.